2004
DOI: 10.1111/j.0307-6946.2004.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Host selection patterns in insects breeding in bracket fungi

Abstract: Abstract.  1. Fungivorous insects are generally viewed as polyphagous, largely because most fungal fruiting bodies constitute an unpredictable resource. To examine the validity of this hypothesis, and degree of phylogenetic relatedness between the preferred hosts of the insects, host selection in the insect fauna of bracket fungi was studied, using data obtained both from the field and the literature. 2. More than half (53%) of the insect species breeding in them appeared to be monophagous. 3. Modern phylogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 28 publications
4
81
0
Order By: Relevance
“…For invertebrates as well as vertebrates (Lawrence 1989;Johnson 1996) fungi display an important source for nutrition as they concentrate valuable nutrients about 10 times higher than the wood they grow on (Martin 1979;Jonsell and Nordlander 2004). It was suggested for a long time that host aroma compounds might play an important role during the colonization of fruiting bodies (Lawrence 1973;Nordlander 1995, 2004), but investigations of such interactions were sparse.…”
Section: Discussionmentioning
confidence: 99%
“…For invertebrates as well as vertebrates (Lawrence 1989;Johnson 1996) fungi display an important source for nutrition as they concentrate valuable nutrients about 10 times higher than the wood they grow on (Martin 1979;Jonsell and Nordlander 2004). It was suggested for a long time that host aroma compounds might play an important role during the colonization of fruiting bodies (Lawrence 1973;Nordlander 1995, 2004), but investigations of such interactions were sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous insects live in close association with fungi, illustrated for example by F. fomentarius. Comparative studies revealed this typical beech forest fungus as one of the most insect species-rich fungi concerning Lepidoptera and Coleoptera (Jonsell and Nordlander 2004). If this fungus (see Table 4), once the most common in natural beech forests (Schmid and Helfer 1999), is reduced significantly, then many dependent species lose an essential habitat resource.…”
Section: Discussionmentioning
confidence: 99%
“…Durable, perennial fruit bodies support a larger proportion of associated monophagous insects than what are found in more short-lasting basidiocarp types. Perennial fungi provide a continuously available resource for Coleoptera, as Jonsell & Nordlander (2004) show with four perennial species (Fomes fomentarius, Fomitopsis pinicola, Ganoderma lipsiense, and Phellinus igniarius) vs. annual sturdy (Inonotus radiatus) and hibernating (Piptoporus betulinus) polypores. Komonen (2003) provided data on beetles of two red-listed polypores in Finland: perennial Fomitopsis rosea and annual ephemeral Amylocystis lapponica.…”
Section: What Happens Within a Polypore In The Course Of Time?mentioning
confidence: 98%